Tumoral Malignancy Decreases Coupled with Higher ROS and Lipid Peroxidation in HCT116 Colon Cancer Cells upon Loss of PRDX6 - Daniel J. Lagal; Antonio M. Montes-Osuna; Alberto Ortiz-Olivencia; Candela Arribas-Parejas; Ángel Ortiz-Alcántara; Cristina Pescuezo-Castillo; José Antonio Bárcena; Carmen Alicia Padilla; Raquel Requejo-Aguilar (MDPI AG, 2024)
Peroxiredoxin 6 (PRDX6) is an atypical member of the peroxiredoxin family that presents not only peroxidase but also phospholipase A2 and lysophosphatidylcholine acyl transferase activities able to act on lipid hydroperoxides of cell membranes. It has been associated with the proliferation and invasive capacity of different tumoral cells including colorectal cancer cells, although the effect of its removal in these cells has not been yet studied. Here, using CRISPR/Cas9 technology, we constructed an HCT116 colorectal cancer cell line knockout for PRDX6 to study whether the mechanisms described for other cancer cells in terms of proliferation, migration, and invasiveness also apply in this tumoral cell line. HCT116 cells lacking PRDX6 showed increased ROS and lipid peroxidation, a decrease in the antioxidant response regulator NRF2, mitochondrial dysfunction, and increased sensitivity to ferroptosis. All these alterations lead to a decrease in proliferation, migration, and invasiveness in these cells. Furthermore, the reduced migratory and invasive capacity of HCT116 cancer cells is consistent with the observed cadherin switch and decrease in pro-invasive proteins such as MMPs. Therefore, the mechanism behind the effects of loss of PRDX6 in HCT116 cells could differ from that in HepG2 cells which is coherent with the fact that the correlation of PRDX6 expression with patient survival is different in hepatocellular carcinomas. Nonetheless, our results point to this protein as a good therapeutic target also for colorectal cancer.